Impacts of an urban flood control infrastructure on the limnology and ichthyofauna of a basaltic Cuesta stream (southeast Brazil) - Siva, L. A. [UNESP]; Kimura, R. S.Y. [UNESP]; Brambilla, E. M. [UNESP]; Silva, S. O. [UNESP]; Nogueira, M. G. [UNESP] (FapUNIFESP (SciELO), 2023)
Strategies for flood control associated to extreme precipitation events in urban areas are urgent, in order to prevent not only material damages but also to avoid human losses. The construction of flood contention reservoirs (“piscinões”) has become a common engineering intervention in urban and peri-urban areas. However, there is a lack of studies focused on the evaluation of environmental impacts of this type of construction. This study intended to verify the ecological effects of a retention reservoir built directly on the course of the Cascata stream, Botucatu (SP). Three sampling sites were selected, located upstream the reservoir, in the reservoir and downstream. Samplings were carried out in July (winter – dry) and November (late spring – rainy) 2020. In situ measurements were obtained through a multiparameter probe (temperature, pH, electrical conductivity, dissolved oxygen, total dissolved solids, and oxidation-reduction potential) and water samples were collected for laboratory determinations (nitrogen, total phosphorus, thermotolerant coliforms, and chlorophyll-a). For fish sampling, manual trawls, sieves and hand nets were used, with a sampling effort of 10 throws per artefact and site. Despite the small distance between the sampling points (~1,300 m) considerable changes in the limnological conditions and fish community structure were observed. The studied environment is originally a small river surrounded by riparian forest, but this characteristic was abruptly changed in the reservoir stretch, with the direct exposition of a much larger water surface to intense solar radiation and atmosphere exchanges. Consequently, as evidenced by the PCA analysis, there was a considerable (stream-reservoir increase) of temperature, dissolved oxygen and chlorophyll. However, this spatial trend was partially disturbed by an accidental sewage-pipe rupture (posteriorly fixed) adjacent to the first sampling point, due to a previous event of extreme precipitation, which resulted in increased values of nutrients, chlorophyll, conductivity and thermotolerant coliforms. Eleven fish species were collected (two non-native), belonging to seven families and five orders. The upstream reference point (despite not be pristine), was characterized by the predominance of native species, while the reservoir condition favored the development of large populations of the non-native species. Despite the urgency of effective actions to prevent floods in urban areas, construction of contention reservoirs directly on stream courses should be avoided, due to their negative ecological impacts.
Impactos de uma infraestrutura para controle de cheias urbanas sobre a limnologia e ictiofauna de um riacho de Cuesta basáltica (sudeste do Brasil)
Keywords: contention reservoir; fluvial interruption; non-native species proliferation; “piscinão”